2014
DOI: 10.1167/iovs.13-12706
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Persistent Hyperplastic Primary Vitreous in Ephrin-A5−/−Mice

Abstract: Ephrin-A5 is a critical factor that regulates primary vitreous regression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 83 publications
0
14
0
1
Order By: Relevance
“…However, since previously, we have reported that ephrin-A5 −/− mice developed ocular abnormalities [55, 56], we wanted to confirm that the lack of aggression is not due to the inability of the mice to see the intruder. Indeed, ephrin-A5 −/− mice, despite the vision impairments, investigated the intruder when introduced into their home cage, suggesting that they were able to sense the presence of another animal in their cage.…”
Section: Discussionmentioning
confidence: 99%
“…However, since previously, we have reported that ephrin-A5 −/− mice developed ocular abnormalities [55, 56], we wanted to confirm that the lack of aggression is not due to the inability of the mice to see the intruder. Indeed, ephrin-A5 −/− mice, despite the vision impairments, investigated the intruder when introduced into their home cage, suggesting that they were able to sense the presence of another animal in their cage.…”
Section: Discussionmentioning
confidence: 99%
“…PFV has been reported in other mammalian species, particularly in dogs [911] and in genetic mouse models [1220]. Studies with these animals have helped immensely with our current understanding of the disease.…”
Section: Persistent Fetal Vasculature (Pfv)mentioning
confidence: 99%
“…Two issues in the commercialization of AO retinal imaging techniques are cost and the space required for such instruments. Efforts have been made to make AO-assisted instruments such as the AOSLO [ 22 24 ], the AO-OCT [ 22 , 23 , 25 ] and the AO fundus camera [ 25 ] more compact and therefore easier to adopt in the clinic. Such efforts indicate that the development of more compact systems is beneficial for the wider use of AO retinal imaging technologies.…”
Section: Introductionmentioning
confidence: 99%